Enhanced Arctic Sea Ice Drift Estimation Merging Radiometer and Scatterometer Data - Girard-ardhuin, Fanny; Ezraty, Robert (IEEE Transactions on Geoscience and Remote Sensing, 2012)
Satellites enable daily and global coverage of the polar oceans and provide a unique monitoring capability of sea ice dynamics. Sea ice drift maps can be estimated in Arctic from several satellite sensors, particularly from scatterometers and radiometers. This study presents the benefits of combining single drift fields at the same resolution into a "merged" field, built at three-and six-day lags during winters with a 62.5-km resolution. It is shown that combining these drift fields not only increases the reliability of the displacement estimation and the number of estimated vectors to almost a full ice covered area but also expands the time period over which these estimations are reliable from freeze until the melt onset. The autumn-winter-spring sea ice drift fields presented here are systematically produced at Institut Francais de Recherche pour l'Exploitation de la Mer/Centre d'Exploitation et de Recherche Satellitaire, the sea ice drift 1992-2011 time series is available, and the processing is ongoing. These data are available for operational use and for the scientific community.